Diogenes «the Cynic»: between anecdote and history - Terceiro Sanmartín, Nerea (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2019)
The present work analyzes the validity of the χρεῖαι or ‘anecdotes’ about Diogenes of Sinope (413 - 323 a.C.) as a source for his study from a historical point of view, taking into account the existing debate on the subject. The characteristics of the χρεία are studied from the rethorical theory perspective, confirming the importance of the expression of the circumstances of the anecdote. In view of this, it is pointed out that those χρεῖαι about Diogenes that have a spatial or topical content, considered homogeneously, align with identifiable contexts in the Fourth-Century B.C. Athens which, furthermore, agree with Diogenes’ legal status as metic and his communicative strategy as cynic. This correspondence would give the anecdotes, at least, a certain plausibility, since they show a coherent and recognizable historical context in democratic Athens.
Keywords: χρεία; anecdote; History; Diogenes of Sinope; Diogenes Laertius; cynics; place; memory; metic; Athens; plausibility